2008
DOI: 10.1104/pp.107.111484
|View full text |Cite
|
Sign up to set email alerts
|

Herbivore-Induced Callose Deposition on the Sieve Plates of Rice: An Important Mechanism for Host Resistance    

Abstract: The brown planthopper (Nilaparvata lugens Stål; BPH) is a specialist herbivore on rice (Oryza sativa) that ingests phloem sap from the plant through its stylet mouthparts. Electronic penetration graphs revealed that BPH insects spent more time wandering over plants carrying the resistance genes Bph14 and Bph15, but less time ingesting phloem than they did on susceptible plants. They also showed that their feeding was frequently interrupted. Tests with [ 14 C]sucrose showed that insects ingested much less phloe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
279
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(305 citation statements)
references
References 53 publications
10
279
0
Order By: Relevance
“…Studies have reported that plants up-regulate callose synthase, β-1,3-glucanase, and polygalacturonase in response to herbivore attack, which are also found in insect saliva [23,32].…”
Section: Cell Wall Modificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have reported that plants up-regulate callose synthase, β-1,3-glucanase, and polygalacturonase in response to herbivore attack, which are also found in insect saliva [23,32].…”
Section: Cell Wall Modificationmentioning
confidence: 99%
“…Infestation by brown plant hopper (Nilaparvata lugens Stal; BPH), a phloem feeder in rice resulted in increased callose deposition at the site of stylet penetration in sieve tubes coupled with up-regulation of transcripts encoding β-1,3-glucanases to unplug sieve tube occlusion [32]. The expression patterns of β-1,3-glucanase genes in BPH susceptible plants following infestation was much higher compared to plants carrying two resistant genes, one of them is a potential R gene [14,32]. Our results agree with these findings where SB showed increased expression of three β-1,3-glucanase related transcripts at 24 and 48 hai (Fig.…”
Section: Cell Wall Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…If mature phloem elements are damaged, massive callose synthesis occurs on the sieve plate, resulting in occlusion of the pores and retention of phloem contents behind the callose plugs (Evert and Derr, 1964;Hao et al, 2008;Mullendore et al, 2010). Indeed, because callose is formed very rapidly upon damage to the phloem, its existence in sieve plate pores in undamaged plants has been disputed in the past: some authors have argued that its presence is an artifact of sectioning and preparation techniques (Evert and Derr, 1964;Walsh and Melaragno, 1976;Spanner, 1978;Sjö lund, 1997; for summary, see van Bel, 2003).…”
mentioning
confidence: 99%
“…The recognition of MAMPs through specific plant receptors triggers the activation of a collaborative defense response to restrict pathogen growth. This primary innate immune response includes the induction of mitogen-activated protein kinase signaling, transcriptional reprogramming, production of reactive oxygen species (ROS; Boller and Felix, 2009;Millet et al, 2010), and modifications of cell wall structure via deposition of callose (Hao et al, 2008) or accumulation of Hyp-rich glycoproteins such as extensin (Wojtaszek et al, 1995;Ribeiro et al, 2006). Most of this knowledge has come from a number of studies performed on leaves.…”
mentioning
confidence: 99%